A Retrospective Study on the Clinical, Laboratory, and Nutritional Status of Pediatric Epidermolysis Bullosa in a Tertiary Referral Hospital in West Java, Indonesia - Tsaqilah L; Diana IA; Gondokaryono SP; Effendi RMRA; Suwarsa O; Gunawan H; Hidayah RMN; Dwiyana RF (Dove Medical Press, 2023)
Laila Tsaqilah, Inne Arline Diana, Srie Prihianti Gondokaryono, Raden Mohamad Rendy Ariezal Effendi, Oki Suwarsa, Hendra Gunawan, Risa Milliawati Nurul Hidayah, Reiva Farah Dwiyana Department of Dermatology and Venereology, Dr. Hasan Sadikin General Hospital, Faculty of Medicine Universitas Padjadjaran, Bandung, IndonesiaCorrespondence: Laila Tsaqilah, Department of Dermatology and Venereology Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin General Hospital, Jl. Pasteur 38, Bandung, West Java, 40161, Indonesia, Tel +62 222032426 ext. 3449, Fax +62 222032426, Email laila.tsaqilah@gmail.comBackground: Epidermolysis bullosa (EB) is a genodermatosis disease with bullae and erosions of the skin and mucous membrane that can last for a lifetime and decrease quality of life. Oral and gastrointestinal disorders inhibit the patients' ability to achieve optimal nutrition, making the patients prone to infection, leading to prolonged wound healing, and delayed growth and developmental process. However, there has been no research on the clinical, laboratory, and nutritional status of pediatric EB patients in Indonesia.Purpose: This study aims to describe the clinical, laboratory, and nutritional characteristics of pediatric EB patients treated in Dr. Hasan Sadikin General Hospital Bandung, Indonesia.Patients and Methods: This was a retrospective descriptive study of pediatric EB patient records in Dermatology and Venereology Outpatient of Dr. Hasan Sadikin General Hospital Bandung, Indonesia, from April 2018-March 2020.Results: Study results showed 12 pediatric EB patients consisting of 7 dystrophic EB (DEB) (4 recessive dystrophic EB [RDEB] patients and 3 dominant dystrophic EB [DDEB]), 3 junctional EB (JEB), and 2 EB simplex (EBS). The most extensive EB wounds was found affecting 10- 20% of the body surface area with a < 10% infected wound area. Pain was found in all patients. The most frequent abnormalities in laboratory examination were anemia and low zinc levels. Severe malnutrition was found in almost half of the patients.Conclusion: RDEB is the most commonly found type of pediatric EB. Wounds on the skin, tooth decay, hand deformity, pain when changing dressings, low zinc levels, and low hemoglobin levels are the clinical features and laboratory findings that contribute to the development of moderate and severe malnutrition in RDEB patients.Keywords: clinical, epidermolysis bullosa, laboratory, nutritional status